Pengembangan Kawasan Bendungan Jatigede Sebagai Objek Daya Tarik Wisata - Hayati, Ristia Nur; Aziz, Firman; Firmansyah, Buyung (JURNAL DESTINASI PARIWISATA; Vol 11 No 1 (2023): VOL 11, NO 1 (2023): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2023.v11.i01.p21, 2023)
The Jatigede Dam area is an area that has great potential as a tourist attraction in Sumedang City. This study aims to identify tourism potential in the Jatigede area and design a strategy for developing the area as a tourist attraction. This study uses a survey method through a quantitative approach, the data obtained is analyzed using a SWOT analysis. The results of the study show that the Jatigede area has great potential to become a superior tourist spot in Sumedang City. However, the area is still experiencing problems in terms of infrastructure. Based on the SWOT analysis, the recommended development strategy is to improve infrastructure, improve promotion and marketing, and develop diverse and quality tourism products. It is hoped that this development strategy can increase the attractiveness of the Jatigede area as a tourist attraction and have a positive impact on the local economy. Keywords: Jatigede Dam, Tourist Attraction, Development, Economy